Wireless power transfer for smart homes and industrial automation - Petryk, Kyrylo (Запоріжжя: НБ ТДАТУ, 2025)
The rapid rate at which smart technologies change requires high power transfer efficiency solutions, so Wireless Power Transfer (WPT) is a revolutionary technology. Without physical connectors, WPT offers enhanced convenience, safety, and automation, changing residential and industrial environments and enabling innovative device connection and system configurations. This article explores WPT's use in smart homes and industrial automation, examining its basic principles, current implementations, advantages, and the barriers to widespread adoption.
Keywords: wireless power; industrial environments; smart home